Cloning and functional analysis of the BrCUC2 gene in Brassica rapa L - Tao, Xiaolei; Zhao, Yuhong; Ma, Li; Wu, Junyan; Zeng, Rui; Jiao, JinTang; Li, Rong; Ma, Weiming; Lian, Yintao; Wang, Wangtian; Pu, Yuanyuan; Yang, Gang; et al. (Frontiers in Plant Science, 2023)
The CUP-SHAPED COTYLEDON2 (CUC2) gene plays an important role in the formation of apical meristem and organ edges in plants. The apical meristematic tissue of Brassica rapa (B. rapa) is associated with cold resistance, however, the role of the CUC2 gene in cold resistance of B.rapa is unclear. we isolated a 1104 bp open reading frame of BrCUC2 from the winter B. rapa cultivar 'Longyou 7'. The BrCUC2 contains a highly conserved domain belonging to the NAM superfamily.Its homologus CUC genes contain similar conserved motifs and are closely related to Brassica oleracea (B.oleracea), and the N-terminal of amino acid sequence contains NAC domain. BrCUC2 protein was localized in the nucleus and self-activation tests showed that pGBKT7-BrCUC2 had selfactivation. Tissue-specific expression analysis and promoter β-Glucuronidase (GUS) activity showed that BrCUC2 had high expression levels in B. rapa growth points and A. thaliana leaf edges, stems and growth points. After low-temperature stress, BrCUC2 showed greater expression in 'Longyou 7,' which presents strong cold resistance and concave growth points, than in 'Longyou 99,' which presents weak cold resistance and protruding growth points. BrCUC2 promoter contains multiple elements related to stress responses. BrCUC2 overexpression revealed that the phenotype did not differ from that of the wild type during the seedling stage but showed weak growth and a dwarf phenotype during the flowering and mature stages. After low-temperature treatment, the physiological indexes and survival rate of BrCUC2-overexpression lines of Arabidopsis thaliana (A. thaliana) were better than those of the wild type within 12 h, although differences were not observed after 24 h. These results showed that BrCUC2 improved the low-temperature tolerance of transgenic A. thaliana within a short time. It can provide a foundation for the study of cold resistance in winter B. rapa.